Penerapan Media Pembelajaran Flash Card untuk Meningkatkan Perkembangan Bahasa Anak - Pradana, Pascalian Hadi; Gerhni, Febrina (JOEAI (Journal of Education and Instruction), 2019)
This study aims to apply flash card learning media to improve children's language development. The method that I use to determine the research area is a purposive sampling. The function of the respondents is through the observation method, supplemented by interview methods and documentation. The results of the study, flash card learning media including attractive card images, easy to play so that children can respond and learn more actively. Flash card media is a teacher's tool for children to play and learn, can also be used at home with their playmates. The results of the school taught by the teacher are very good so that the results of children's language development are good, children can carry out 2-3 simple commands, can imitate sentences that are conveyed and can respond to questions well. Child language development can clearly state words, vocabulary is good and can speak well after the child enters school. Conclusion, the application of flash card learning media can improve children's language development. Keywords: Flash Card Media, Development, Children's Language